GAMBARAN C-REAKTIF PROTEIN (CRP) METODE AGLUTINASI LATEX PADA SIKLUS MENSTRUASI MAHASISWI STIKES HUTAMA ABDI HUSADA TULUNGAGUNG TAHUN 2021 - Nosa Ika Cahyariza (Medical Laboratory Analysis and Sciences Journal, 2022)
C-Reactive Protein (CRP) is an acute phase protein that is present in normal serum even in small amounts. In certain circumstances with an inflammatory reaction or tissue damage (necrosis) caused by infectious and non-infectious diseases. One of the causes of inflammation is menstruation. Menstruation is periodic bleeding in the uterus starting about 14 days of ovulation. This study aimed to determine CRP levels in the menstrual cycle of STIKes Hutama Abdi Husada Tulungagung students in 2021. This type of research is descriptive with the number of respondents 17 female students. The samples in this study were 17 serum samples of students from the Medical Laboratory Technology Study Program of STIKes Hutama Abdi Husada Tulungagung using the Purposive Sampling technique with data analysis using percent (%) to determine whether or not there was agglutination in the serum of female students who were menstruating. The results of this study are presented in tabular form. In the qualitative examination, the agglutination was positive with a percentage of 6% and negative agglutination with a percentage of 94% in the serum samples of the STIKes Hutama Abdi Husada Tulungagung student in 2021. Based on the results of this study, it can be said that there is no increase in CRP levels in the menstrual cycle of STIKes Hutama Abdi Husada Tulungagung students in 2021.